2009
DOI: 10.1175/2009jhm1066.1
|View full text |Cite
|
Sign up to set email alerts
|

A Modeling and Observational Framework for Diagnosing Local Land–Atmosphere Coupling on Diurnal Time Scales

Abstract: Land-atmosphere interactions play a critical role in determining the diurnal evolution of both planetary boundary layer (PBL) and land surface temperature and moisture states. The degree of coupling between the land surface and PBL in numerical weather prediction and climate models remains largely unexplored and undiagnosed due to the complex interactions and feedbacks present across a range of scales. Further, uncoupled systems or experiments (e.g., the Project for Intercomparison of Land Parameterization Sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
177
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 185 publications
(182 citation statements)
references
References 75 publications
(71 reference statements)
5
177
0
Order By: Relevance
“…By incorporating CRMs, SPCAM explicitly resolves convection and improves the precipitation simulation in many aspects, which alters soil moisture variability. To better understand the effects of explicitly resolved convection on the surface flux response to soil moisture variability, more constrained experiments and land-atmosphere coupling studies at subdaily scales and at process levels (e.g., the mixing diagram approach in Santanello et al [2009]) would be useful.…”
Section: Journal Of Advances In Modeling Earth Systems 101002/2016msmentioning
confidence: 99%
See 1 more Smart Citation
“…By incorporating CRMs, SPCAM explicitly resolves convection and improves the precipitation simulation in many aspects, which alters soil moisture variability. To better understand the effects of explicitly resolved convection on the surface flux response to soil moisture variability, more constrained experiments and land-atmosphere coupling studies at subdaily scales and at process levels (e.g., the mixing diagram approach in Santanello et al [2009]) would be useful.…”
Section: Journal Of Advances In Modeling Earth Systems 101002/2016msmentioning
confidence: 99%
“…As the results show, the sensitivity terms (surface fluxes response to soil moisture or rainfall response to surface fluxes) in the coupling indices play dominant roles in many cases. To better understand these effects of superparameterization at a process level, we report in a separate manuscript the results of applying a local land-atmosphere coupling (LoCo) framework [Santanello et al, 2009[Santanello et al, , 2011a in observationally constrained SPCAM and CAM experiments.…”
mentioning
confidence: 99%
“…This comprehensive analysis extends from the work of Santanello et al (2009 hereafter referred to as S09 and S11) by performing an evaluation using observations along with composite and regional (including reanalysis product) analyses. The case studies chosen for these experiments are composed of extreme dry and wet conditions in terms of soil moisture and precipitation relative to normal, and are therefore ideally suited to capture a wide range of variability in L-A interactions and coupling.…”
Section: Introductionmentioning
confidence: 91%
“…This was performed in a global climate model context using a large number of ensemble simulations, and therefore parsing out the reasons for differences in coupling strength amongst models (and inherent land surface and PBL physics) remains a difficult task. A companion effort has since been launched that focuses on local L-A coupling (LoCo; Santanello et al 2009 in coupled models by diagnosing land-PBL interactions at the process level using a regional, high-resolution testbed. The methodology developed in LoCo can be applied to any model or observations, and it is particularly well suited to isolate the impacts of land surface perturbations on the PBL (and vice-versa) that are crucial for sustaining flood and drought conditions.…”
Section: Introductionmentioning
confidence: 99%
“…where EF is the evaporative fraction, defined as feedback of the atmosphere (through the PBL) on surface fluxes (EF atm ) (Santanello et al 2007;249 van Heerwaarden et al 2009 of LoCo research and the related diagnostic framework can be found in Santanello et al (2009Santanello et al ( , 263 2011aSantanello et al ( , 2011bSantanello et al ( , 2012; hereafter referred to as S09, S11a, S11b, S12 OPT/UE) algorithms to be applied to the LSMs to exploit further the information content from 296 observations. The algorithms (e.g.…”
mentioning
confidence: 99%